2020
DOI: 10.3389/fendo.2020.00341
|View full text |Cite
|
Sign up to set email alerts
|

P2Y2 Receptor Promotes High-Fat Diet-Induced Obesity

Abstract: P2Y 2 , a G protein-coupled receptor (R), is expressed in all organs involved in the development of obesity and insulin resistance. To explore the role of it in diet-induced obesity, we fed male P2Y 2-R whole body knockout (KO) and wild type (WT) mice (B6D2 genetic background) with regular diet (CNT; 10% calories as fat) or high-fat diet (HFD; 60% calories as fat) with free access to food and water for 16 weeks, and euthanized them. Adjusted for body weights (BW), KO mice consumed modestly, but significantly m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 57 publications
3
27
0
Order By: Relevance
“…Current treatment strategies aim to improve hepatic steatosis and inflammation by reducing insulin resistance and oxidative stress in obesity-induced NAFLD [ 5 ]. P2Y2R is widely expressed in metabolic organs, such as liver, white adipose tissue and skeletal muscle [ 20 , 21 , 22 ]. P2Y2R activation is involved in various hepatic cellular processes of proliferation, apoptosis, inflammation, and fibrosis [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Current treatment strategies aim to improve hepatic steatosis and inflammation by reducing insulin resistance and oxidative stress in obesity-induced NAFLD [ 5 ]. P2Y2R is widely expressed in metabolic organs, such as liver, white adipose tissue and skeletal muscle [ 20 , 21 , 22 ]. P2Y2R activation is involved in various hepatic cellular processes of proliferation, apoptosis, inflammation, and fibrosis [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…P2Y2R activation is involved in various hepatic cellular processes of proliferation, apoptosis, inflammation, and fibrosis [ 32 , 33 , 34 ]. A recent study has reported that P2Y2R promotes HFD-induced obesity and insulin resistance by stimulating adipogenesis and inflammatory cytokines, and altering adipokine production and lipid metabolism in adipose tissue [ 22 ]. Consistently, P2Y2R deficient mice inhibit excessive immune cell infiltration, reducing adipose tissue inflammation and ameliorating the HFD-induced metabolic phenotype [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TSPAN14 (Tetraspanin 14) can interact with ADAM10 (ADAM Metallopeptidase Domain 10) and then regulate leukocyte development and in ammatory immunity function 54 . Previous studies have demonstrated that P2RY2 (Purinergic Receptor P2Y2) contributes to the development of chronic high-fat diet-induced metabolic dysfunction and insulin resistance 55,56 . Besides, Merz et al suggested that P2RY2 is involved in the process of immune cell in ltration in metabolic syndrome 57 .…”
Section: Discussionmentioning
confidence: 99%